Investigating the Secondary Care System Burden of Glycogen Storage Disease Type Ia (GSDIa) Using the Hospital Episode Statistics Database - Eliza Kruger; Shreena Giblin (Journal of Health Economics and Outcomes Research)
# Background Glycogen storage disease type Ia (GSDIa) is a rare, inherited metabolic disorder characterized by a deficiency in glucose 6-phosphatase. People living with GSDIa are at high risk for clinical manifestations (including hypoglycemia and hepatomegaly) and clinical complications (including hyperlipidemia, stunted growth, liver adenomas, and renal failure). Evaluating symptom management and secondary care burdens is vital to understanding the patient experience and optimizing care pathways.